Dinâmica do sistema radical de uma pastagem do bioma Pampa sob diferentes intervalos de pastejo - Herbstrith, Nathália Brum (2019)
Currently in Brazil there are six different biomes, being the Pampa biome present only in Rio Grande do Sul. This biome has a very large diversity of grass species and other botanical families of interest. It occupies about 63% of the state and many studies point out the importance of its aerial biomass, but little is known about the root systems of the species composing this biome. Depending on the interactions that occur between species and the way they are managed, the radical system responds in different ways, and its study is extremely important. Therefore, the objective of this work was to evaluate the growth and distribution of roots in the soil profile in a natural grassland managed under rotational grazing with two defoliation intervals, at a depth 0 - 60 cm through a non destructive method of root analysis, Minirhizotron. and test the use of RootSnap software for image processing. The experiment was conducted in a natural pasture area belonging to the Federal University of Santa Maria, Depressão Central of Rio Grande do Sul. Treatments were based on the thermal sum required for the leaf elongation duration of two distinct groups of native grasses: 375 and 750 degree days (GD). Images were obtained through the CI-600 In-Situ Root Imager scanner and analyzed by the 690 RootSnap software and compared to other methods in the literature to test the validity of the methodology employed and to evaluate the root growth dynamics. Above-ground plant material cuts were performed to simulate animal grazing at each thermal sum, where two image collections were performed, one in spring and one in summer. Field images obtained by the CI 600 In-Situ Root Imager scanner were imported and processed by the 690 RootSnap software. Data were exported and subjected to multivariate ordination analysis by the principal coordinate method, cluster analysis and variance analysis by randomization tests, with Euclidean distance as a measure of similarity using the MULTIV software. The Minirhizotron technique was efficient in monitoring the development of the radical system of native grasses during the spring and summer period of the years 2017/18, as long as the period of accommodation of acrylic tubes in the soil is respected. The use of the 690 RootSnap software was also efficient, but with only one image collection per season due to the need for time and more manpower during image processing in the software. It was found that the variables length, area, volume and diameter were influenced by the delay in the winter months and the management history adopted in the area.